Basic Materials for Manufacturing Wood-Plastic Composites - Nikola Španić (University of Zagreb, Faculty of Forestry and Wood Technology, 2010)
This paper summarizes and systemizes research results of the characteristics of the basic materials for manufacturing wood-plastic composites (WPC). The properties of wood and polymer materials are discussed as well as their impact on processing, physical and mechanical properties and composite properties under conditions of use. WPCs have very good properties in different conditions of use, and they proved to be one of the solutions for proper disposal of ever increasing quantities of organic and plastic residues. Specific features of certain types of the basic organic and plastic materials, the possibility of their modifi cation and combination of materials, enable the production of different types of composites, and also of forming final products of specific characteristics. Due to the presence of synthetic polymers and additives for structural improvement of composites, these materials are not completely environmentally friendly, but efforts should be taken to improve the WPCs and generally to increase their use.